2023
DOI: 10.1002/ppp3.10470
|View full text |Cite
|
Sign up to set email alerts
|

Targeted improvement of plant‐based protein: Genome‐wide association mapping of a lentil (Lens culinaris Medik.) diversity panel

Nathan Johnson,
J. Lucas Boatwright,
William Bridges
et al.

Abstract: Societal Impact StatementThe world is increasingly looking to plant‐based sources to meet its protein needs. Multiple factors are driving this progression, ranging from nutritional and ethical considerations to climate change and population growth. As a pulse crop, lentil is ideal to help meet this change in demand. However, plant‐based proteins have limiting amino acids and lower protein digestibility compared to animal‐based proteins. This research identifies genetic markers that can be used to accelerate br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
0
3
1
Order By: Relevance
“…As a complex quantitative trait, protein concentration is controlled by many genes with small effects; consequently, we were able to identify many potential markers for use in local lentil breeding programs (Supplemental Figure 5). In comparison to the results from Johnson et al (2023), we identified only one marker (Lcu.2RBY.Chr5p155854268) within 300 kbp of their QTLs, emphasizing the importance of the environment for identifying markers for breeding purposes. We recommend future studies sample an even broader range of environments to dissect the genes influencing protein concentration.…”
Section: Genome-wide Association Studies On Protein and Amino Acid Co...contrasting
confidence: 55%
See 2 more Smart Citations
“…As a complex quantitative trait, protein concentration is controlled by many genes with small effects; consequently, we were able to identify many potential markers for use in local lentil breeding programs (Supplemental Figure 5). In comparison to the results from Johnson et al (2023), we identified only one marker (Lcu.2RBY.Chr5p155854268) within 300 kbp of their QTLs, emphasizing the importance of the environment for identifying markers for breeding purposes. We recommend future studies sample an even broader range of environments to dissect the genes influencing protein concentration.…”
Section: Genome-wide Association Studies On Protein and Amino Acid Co...contrasting
confidence: 55%
“…Kumar et al (2016) found that both Mediterranean landraces and wild lentil species had higher protein concentration than Indian varieties and breeding lines and, therefore, could be used as a breeding source for increased protein concentration. A diversity panel of cultivated lentil grown under greenhouse conditions had a range of mean total amino acid concentration of 18-36 % with some genetic clusters having higher concentrations of specific amino acids than others (Johnson et al, 2023). In Canada, the smaller red cotyledon lentils tend to show slightly higher protein concentration than the larger yellow cotyledon (green) lentils (Boye et al, 2010;Subedi et al, 2021;Wang, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), chickpeas (Cicer arietinum L.), common beans (Phaseolus vulgaris L.), lentils (Lens culinaris Medikus) and cowpeas (Vigna unguiculata L. Walp). This is because pulses are high in protein (>20%), dietary fibre and micronutrients, such as folate, iron, zinc, magnesium, potassium and selenium, with <3% fat content [16][17][18][19]. Pulses contain high-quality amino acids distributed proportionately within the different classes, and consequently benefit the consumer nutritionally, therapeutically and techno-functionally.…”
Section: Introductionmentioning
confidence: 99%